The Effects of Pregnancy Status on Lacrimal Caruncle Temperature, Intraocular Pressure and Rectal Temperature in Cats: A Preliminary Study - Candemir Ozcan; Tarik Safak; Ayse Basak Dellalbasi; Elif Dogan (Veterinary Medicine and Science)
ABSTRACT Objective The objectives of this study were to compare the body temperatures between pregnant and nonpregnant cats from two sites, lacrimal caruncle temperature (LCT) and rectal temperature (RT), and to compare intraocular pressure (IOP) between pregnant and nonpregnant cats. Animal studied This study was performed on 13 pregnant and 16 anoestrous cats. Procedures The gestation period of the pregnant cats ranged from 20 to 45 days. A vaginal smear was also performed to determine the sexual cycles of nonpregnant cats. The IOP was measured using a rebound tonometer. Results The pregnant cats (38 ± 0.7°C) exhibited a lower RT than the nonpregnant cats (38.5 ± 0.5°C) (p < 0.05). No significant differences existed between the pregnant and nonpregnant groups in the right (R)‐LCT or left (L)‐LCT (p > 0.05). The average LCT temperature measured 32.30 ± 2.23°C in cats. The right (R)‐IOP in pregnant cats (17.69 ± 5.6 mm Hg) was significantly lower than in nonpregnant cats (22.37 ± 5.27 mm Hg) (p < 0.029). Pregnant cats exhibited a significantly lower left (L)‐IOP value (17.69 ± 5.76 mm Hg) compared to nonpregnant cats (23.18 ± 5.55 mm Hg) (p < 0.015). Conclusion This study presents a preliminary report that documents a noteworthy reduction in RT in pregnant cats (38 ± 0.7°C) as compared to cats in anoestrus. Pregnancy also has an effect on the IOP. It was hypothesised that the hormonal changes induced by pregnancy in cats would have a substantial impact on IOP and RT. Although body temperature can be measured using LCT, RT should still be utilised as the reference measurement site.